Multidrug-Resistant Tuberculosis: Treatment and Outcomes of 93 Patients - Sarah K Brode; Robert Varadi; Jane McNamee; Nina Malek; Sharon Stewart; Frances B Jamieson; Monica Avendano (Canadian Respiratory Journal)
BACKGROUND: Tuberculosis (TB) remains a leading cause of death worldwide and the emergence of multidrug-resistant TB (MDR TB) poses a threat to its control. There is scanty evidence regarding optimal management of MDR TB. The majority of Canadian cases of MDR TB are diagnosed in Ontario; most are managed by the Tuberculosis Service at West Park Healthcare Centre in Toronto. The authors reviewed 93 cases of MDR TB admitted from January 1, 2000 to December 31, 2011.